Association of the transcobalamin II gene 776C→G polymorphism with Alzheimer's type dementia: dependence on the 5, 10-methylenetetrahydrofolate reductase 1298A→C polymorphism genotype. (July 2015) - Cascalheira, José F; Gonçalves, Mónica; Barroso, Madalena; Castro, Rita; Palmeira, Manuela; Serpa, André; Dias-Cabral, Ana C; Domingues, Fernanda C; Almeida, Sofia
Background: Decreased serum concentrations of vitamin B12 are associated with Alzheimer's type dementia. The transcobalamin II gene (TCN2) 776C→G polymorphism affects transcobalamin II function as a carrier of vitamin B12 and might modify its availability. The association of the TCN2 776C→G polymorphism with Alzheimer's type dementia is unclear and was investigated in the present study. Methods: Case–control study including 27 individuals diagnosed with Alzheimer's type dementia and 28 healthy controls. Serum concentrations of vitamin B12, homocysteine and other analytes were determined and the presence of TCN2 776C→G and 5, 10-methylenetetrahydrofolate reductase 1298A→C polymorphisms genotypes was ascertained by polymerase chain reaction–restriction fragment length polymorphism. Results: Serum concentrations of vitamin B12 were lower while those of homocysteine were higher in patients than in controls ( P  < 0.05). The frequency of individuals carrying at least one 5, 10-methylenetetrahydrofolate reductase 1298C allele was higher (59% versus 32%) while frequency of individuals harbouring at least one TCN2 776G allele was lower (58% versus 86%) in patients than in controls ( P  < 0.05). Univariate logistic regression showed negative association of TCN2 776CG genotype with Alzheimer's type dementia (OR = 0.17 versus CC genotype, P  < 0.02). Multivariate logistic regression identified TCN2 776C→G polymorphism as independent predictor of Alzheimer's type dementia together with higher concentrations of homocysteine, cholesterol and uric acid and lower concentrations of oestradiol. Association of TCN2 776C→G polymorphism with Alzheimer's type dementia was observed for individuals carrying the 5, 10-methylenetetrahydrofolate reductase 1298AA genotype but not the AC or CC genotypes, indicating interaction between the two polymorphisms. Conclusions: The TCN2 776C→G polymorphism is negatively associated with Alzheimer's type dementia, suggesting a protective role against the disease in subjects with the 5, 10-methylenetetrahydrofolate reductase 1298AA genotype.